Effects of Neuroplasticity-Based Adaptive Physical Education Learning Model on Motor Development in Early Childhood (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2026)
This study aimed to analyze the influence of the neuroplasticity-based adaptive physical education learning model on motor development in early childhood and to understand teacher experiences in designing and implementing this learning strategy. The study employed a quasi-experimental one-group pretest–posttest design, complemented by a qualitative case study approach. The study participants consisted of 25 children aged 5–6 years and a class teacher at a kindergarten selected purposively. Quantitative data were obtained through motor development tests administered before and after the implementation of adaptive physical education. Quantitative data analysis was conducted using descriptive-comparative analysis to compare pre-test and post-test scores on child motor development. Meanwhile, qualitative data were collected through participant observation, semi-structured interviews, and documentation analyzed using an interactive analysis model that included data reduction, data presentation, and conclusion drawing. The results showed an increase in child motor development scores after the neuroplasticity-based adaptive physical education intervention. Qualitative findings revealed three main themes, namely adaptation of activities to individual child needs, increased self-confidence and involvement in child movement activities, and strengthened social interactions during the learning process. These findings suggest that varied and progressive movement stimulation can support optimal motor development through contextualized learning that is responsive to the characteristics of early childhood. This research provides theoretical contributions to the integration of neuroscience with early childhood physical education, as well as practical implications for the development of more adaptive and evidence-based learning models in early childhood education settings.